2005
DOI: 10.1074/jbc.m507322200
|View full text |Cite
|
Sign up to set email alerts
|

NAP1 Modulates Binding of Linker Histone H1 to Chromatin and Induces an Extended Chromatin Fiber Conformation

Abstract: NAP1 (nucleosome assembly protein 1) is a histone chaperone that has been described to bind predominantly to the histone H2A⅐H2B dimer in the cell during shuttling of histones into the nucleus, nucleosome assembly/remodeling, and transcription. Here it was examined how NAP1 interacts with chromatin fibers isolated from HeLa cells. NAP1 induced a reversible change toward an extended fiber conformation as demonstrated by sedimentation velocity ultracentrifugation experiments. This transition was due to the remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 90 publications
3
62
1
Order By: Relevance
“…A similar process is likely to be in place in plants, whereas a CDK2 type of activity could possibly contribute to H1 phosphorylation in wheat male meiocytes (Greer et al, 2012). In addition, H1 binding is modulated by the histone chaperone NUCLEOSOME ASSEMBLY PROTEIN 1 (NAP1) (Kepert et al, 2005). Arabidopsis plants lacking NAP1;1-3 activity [triple mutant (Liu et al, 2009)] or the activity of the NAP1-related proteins NRP1 and NRP2 [double mutant (Zhu et al, 2006)] show normal eviction of both H1.1 and H1.2 in the MMC and reincorporation at meiosis (supplementary material Fig.…”
Section: Mechanisms Of Chromatin Reprogrammingmentioning
confidence: 99%
“…A similar process is likely to be in place in plants, whereas a CDK2 type of activity could possibly contribute to H1 phosphorylation in wheat male meiocytes (Greer et al, 2012). In addition, H1 binding is modulated by the histone chaperone NUCLEOSOME ASSEMBLY PROTEIN 1 (NAP1) (Kepert et al, 2005). Arabidopsis plants lacking NAP1;1-3 activity [triple mutant (Liu et al, 2009)] or the activity of the NAP1-related proteins NRP1 and NRP2 [double mutant (Zhu et al, 2006)] show normal eviction of both H1.1 and H1.2 in the MMC and reincorporation at meiosis (supplementary material Fig.…”
Section: Mechanisms Of Chromatin Reprogrammingmentioning
confidence: 99%
“…For example, nucleosome assembly protein 1, nucleoplasmin, and Hsp90 induce changes in chromatin conformation that are assumed to increase accessibility for proteinases and nucleases (20)(21)(22)(23)(24)(25). It is not known whether such molecules are tolerated in vivo in doses necessary for a therapeutic effect.…”
mentioning
confidence: 99%
“…The Chz1 chaperone shows very high specificity, binding preferentially to the variant H2A.Z/H2B dimer over the canonical H2A/H2B dimer (10). In contrast, chaperones such as NAP1 can bind all of the core histones as well as the linker histone, although with varying affinities (11)(12)(13). Following the discovery that NAP1 and ACF can facilitate the assembly of chromatin, organizing nucleosomes in regular spaced arrays (14), NAP1 has become a vital constituent for the generation of in vitro chromatin systems (15) in a range of downstream studies (16 -20).…”
mentioning
confidence: 99%
“…In more physiological buffers, further oligomerization of yNAP was observed using size exclusion chromatography (SEC) (12) and AUC (25). Several groups reported that the NAP1 dimer can bind an H3/H4 or H2A/H2B dimer or an H1 monomer (11,12,25,26). Alternative stoichiometries have been suggested, including one NAP1 monomer binding one histone dimer (27,28), and therefore, the question of the NAP1-histone stoichiometry remains controversial.…”
mentioning
confidence: 99%